2018
DOI: 10.22159/ajpcr.2018.v11i10.27245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Role of Varuna (Crataeva Nurvala) Extract on Thyroid Gland and Its Histology Through Iodothyronine Deiodinases

Abstract: Objective: Crataeva nurvala (CN) is used for its therapeutic effects, but its effect on the thyroid gland in euthyroid conditions and mechanism behind its thyrotropic activity in hypothyroidism is still not explored. This study screened the pharmacological effect of the ethanolic extract of the bark of CN on thyroid hormones, free and total thyroxine (FT4 and T4), triiodothyronine (T3), thyroid-stimulating hormone (TSH) levels, and thyroid histology in normal Swiss albino female mice.Methods: Eighteen animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Pre-clinically it has been demonstrated that CN bark extract can elevate free thyroxine (FT4) and lower the raised cholesterol levels (Kaur et al 2017). However the mechanism behind CN thyrotropic activity, mainly via iodothyronine deiodinases, effect on thyroid gland histology and physiological parameters in hypothyroid mice needs to be explored in comparison with its per se effects in normal healthy mice (Kaur et al 2018). So, this study is aimed to evaluate the mechanism of thyroprotective activity and effects on thyroid histopathology and physiological parameters in hypothyroid mice, whose thyroid status was altered by using (6-propyl-2-thiouracil) PTU, as an inducing agent, that selectively inhibits iodothyronine deiodinases type I (DIO1) mediated thyroxine (T 4 ) conversion to Triidothyronine (T 3 ) at thyroid gland and at periphery over iodothyronine deiodinases type II (DIO 2 ) and results in disruption of thyroid histology with physiological changes Moriyama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-clinically it has been demonstrated that CN bark extract can elevate free thyroxine (FT4) and lower the raised cholesterol levels (Kaur et al 2017). However the mechanism behind CN thyrotropic activity, mainly via iodothyronine deiodinases, effect on thyroid gland histology and physiological parameters in hypothyroid mice needs to be explored in comparison with its per se effects in normal healthy mice (Kaur et al 2018). So, this study is aimed to evaluate the mechanism of thyroprotective activity and effects on thyroid histopathology and physiological parameters in hypothyroid mice, whose thyroid status was altered by using (6-propyl-2-thiouracil) PTU, as an inducing agent, that selectively inhibits iodothyronine deiodinases type I (DIO1) mediated thyroxine (T 4 ) conversion to Triidothyronine (T 3 ) at thyroid gland and at periphery over iodothyronine deiodinases type II (DIO 2 ) and results in disruption of thyroid histology with physiological changes Moriyama et al, 2007).…”
Section: Introductionmentioning
confidence: 99%